Blood feeding on large grazers affects the transmission of Borrelia burgdorferi sensu lato by Ixodes ricinus - Pacilly, F.C.A.; Benning, M.E.; Jacobs, F.; Leidekker, J.; Sprong, H.; Van Wieren, S.E.; Takken, W. (Ticks and tick-borne diseases, 2014)
The presence of Ixodes ricinus and their associated Borrelia infections on large grazers was investigated. Carcases of freshly shot red deer, mouflon and wild boar were examined for the presence of any stage of I. ricinus. Questing ticks were collected from locations where red deer and wild boar are known to occur. Presence of Borrelia burgdorferi s.l. DNA was examined in a fraction of the collected ticks. Larvae, nymphs and adult ticks were found on the three large grazers. Red deer had the highest tick burden, with many of the nymphs and adult females attached for engorgement. Most larvae had not attached. The mean number of ticks on the animals varied from 13 to 67. Ticks were highly aggregated amongst the animals: some animals had no ticks, while others had high numbers. Larvae and nymphs were mostly found on the ears, while adult ticks were attached to the axillae. The Borrelia infection rate of questing nymphs was 8.5%. Unengorged wandering nymphs on deer had a Borrelia infection rate of 12.5%, while only 0.9% of feeding nymphs carried a Borrelia infection. The infection rate of unengorged adult male ticks was 4.5%, and that of feeding female ticks was 0.7%. The data suggest that ticks feeding on red deer and wild boar lose their Borrelia infections. The implications of the results are discussed with respect to Borrelia epidemiology and maintenance of a Borrelia reservoir as well as the role of reproductive hosts for Ixodes ricinus.